Systematic Literature Review: Strengthening Teacher Competence through Creative Project-Based STEAM Implementation in Physics Learning - Nadi Suprapto; Utama Alan Deta; Muhammad Nurul Fahmi; Dodik Arwin Dermawan; Dewi Nurmalasari; Hasan Nuurul Hidaayatullaah; Elsa Monica; Adrian Bagas Damarsha; Nina Fajriyah Citra (Studies in Philosophy of Science and Education, 2025)
The STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach is a new form of teaching that places students in real-world situations around them by following the concept of interdisciplinary teaching. STEAM is highly relevant in supporting students' 21st-century skills. As is well known, 21st-century skills encourage students' critical thinking, communication, collaboration, innovation, and creativity. In physics learning, it is not uncommon for students to have difficulty understanding the subject. Teachers, as learning facilitators, are expected to be able to integrate STEAM into physics education. Teachers must have the skills to develop learning tools. Through research using the SLR method, this study aims to investigate the importance of teachers' competencies in implementing project-based STEAM learning in physics education. Project-based learning emphasizes collaborative learning activities among heterogeneous groups of students. The analysis results show that the implementation of the STEAM approach in learning is still limited. Physics teachers are important agents in equipping students with the necessary physics knowledge and scientific investigation skills. Therefore, physics teachers need support in improving their understanding of STEAM. In learning activities involving project-based STEAM, it is known that it can increase students' creativity and innovation in problem solving.